DEMOCRACY AND GOVERNANCE IN THE 21ST CENTURY - Karikante, Ganpat Ramrao (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The 21st century has brought new opportunities and challenges for democracy and governance. With the advancement of technology and the pace of globalization, there has been a radical change in the pace of political participation, accountability and governance. India is the largest active democracy in the world. The reason behind this is not only its vast size, but also its pluralistic nature and its ability to stand the test of time. Democratic traditions and principles are an integral part of Indian culture. Qualities like equality, tolerance, peaceful coexistence and a way of life based on democratic values have existed in our society for centuries. Real democracy has deeply ingrained our political consciousness. Democracy based on principles like equality, representation and participation is undergoing major changes in the 21st century. The rapid spread of information, growing demographics, growing concerns about inequality, and global crises such as climate change and pandemics have tested the resilience of democratic institutions. This article examines the interrelationship between democracy and governance in the 21st century and explores ways to strengthen democracy and governance to meet current challenges. It also explores the development of democracy in the contemporary era, the impact of technological and socio-political changes, and the need for accountable and sustainable systems of governance.